General Features of Public Law – The Slovenian Perspectives - Tičar, Bojan; Maša Tičar, Maša Tičar (University of Maribor Press, 2024)
This book is intended is to be used as an aid in understanding general features of public law from Slovenian perspective. The book has three parts. The first chapter deals with the state, its essential elements,and the various types of states, taking into consideration a range of different criteria. The second chapter introduces the basic constituent parts of the law and the forms of legal order in which these parts are vertically and horizontally incorporated. The terms are sometimes simplified in order to bring law and an understanding of it closer to readers who are not professional lawyers.The third chapter is devoted to defining basic terms of administrative and civil service law. Administrative law consists primarily of the legal norms which regulate the foundations of the organisation of the state and local communities. The last part of this chapter is devoted to civil servants and public salery system.